Establishment of Inducible Wild Type and Mutant Myocilin-GFP-Expressing RGC5 Cell Lines - Ying, Hongyu; Shen, Xiang; Yue, Beatrice Y. J. T. (PLOS ONE, 2012)
Background Myocilin is a gene linked directly to juvenile- and adult-onset open angle glaucoma. Mutations including Gln368stop (Q368X) and Pro370Leu (P370L) have been identified in patients. The exact role of myocilin and its functional association with glaucoma are still unclear. In the present study, we established tetracycline-inducible (Tet-on) wild type and mutant myocilin-green fluorescence protein (GFP) expressing RGC5 stable cell lines and studied the changes in cell migration and barrier function upon induction. Methodology/Principal Findings After several rounds of selection, clones that displayed low, moderate, or high expression of wild type, Q368X or P370L myocilin-GFP upon doxycycline (Dox) induction were obtained. The levels of wild type and mutant myocilin-GFP in various clones were confirmed by Western blotting. Compared to non-induced controls, the cell migration was retarded, the actin stress fibers were fewer and shorter, and the trypsinization time needed for cells to round up was reduced when wild type or mutant myocilin was expressed. The barrier function was in addition aberrant following induced expression of wild type, Q368X or P370L myocilin. Immunoblotting further showed that tight junction protein occludin was downregulated in induced cells. Conclusions/Significance Tet-on inducible, stable RGC5 cell lines were established. These cell lines, expressing wild type or mutant (Q368X or P370L) myocilin-GFP upon Dox induction, are valuable in facilitating studies such as proteomics, as well as functional and pathogenesis investigations of disease-associated myocilin mutants. The barrier function was found impaired and the migration of cells was hindered with induced expression of wild type and mutant myocilin in RGC5 cell lines. The reduction in barrier function might be related to the declined level of occludin. The retarded cell migration was consistent with demonstrated myocilin phenotypes including the loss of actin stress fibers, lowered RhoA activities and compromised cell-matrix adhesiveness.